Carbon Monoxide Exerts Functional Neuroprotection After Cardiac Arrest Using Extracorporeal Resuscitation in Pigs. Issue 4 (April 2020) - Wollborn, Jakob; Steiger, Christoph; Doostkam, Soroush; Schallner, Nils; Schroeter, Nils; Kari, Fabian A.; Meinel, Lorenz; Buerkle, Hartmut; Schick, Martin A.; Goebel, Ulrich
Abstract : Objectives: Neurologic damage following cardiac arrest remains a major burden for modern resuscitation medicine. Cardiopulmonary resuscitation with extracorporeal circulatory support holds the potential to reduce morbidity and mortality. Furthermore, the endogenous gasotransmitter carbon monoxide attracts attention in reducing cerebral injury. We hypothesize that extracorporeal resuscitation with additional carbon monoxide application reduces neurologic damage. Design: Randomized, controlled animal study. Setting: University research laboratory. Subjects: Landrace-hybrid pigs. Interventions: In a porcine model, carbon monoxide was added using a novel extracorporeal releasing system after resuscitation from cardiac arrest. Measurements and Main Results: As markers of cerebral function, neuromonitoring modalities (somatosensory-evoked potentials, cerebral oximetry, and transcranial Doppler ultrasound) were used. Histopathologic damage and molecular markers (caspase-3 activity and heme oxygenase-1 expression) were analyzed. Cerebral oximetry showed fast rise in regional oxygen saturation after carbon monoxide treatment at 0.5 hours compared with extracorporeal resuscitation alone (regional cerebral oxygen saturation, 73% ± 3% vs 52% ± 8%; p < 0.05). Median nerve somatosensory-evoked potentials showed improved activity upon carbon monoxide treatment, whereas post–cardiac arrest cerebral perfusion differences were diminished. Histopathologic damage scores were reduced compared with customary resuscitation strategies (hippocampus: sham, 0.4 ± 0.2; cardiopulmonary resuscitation, 1.7 ± 0.4; extracorporeal cardiopulmonary resuscitation, 2.3 ± 0.2; extracorporeal cardiopulmonary resuscitation with carbon monoxide application [CO-E-CPR], 0.9 ± 0.3; p < 0.05). Furthermore, ionized calcium-binding adaptor molecule 1 staining revealed reduced damage patterns upon carbon monoxide treatment. Caspase-3 activity (cardiopulmonary resuscitation, 426 ± 169 pg/mL; extracorporeal cardiopulmonary resuscitation, 240 ± 61 pg/mL; CO-E-CPR, 89 ± 26 pg/mL; p < 0.05) and heme oxygenase-1 (sham, 1 ± 0.1; cardiopulmonary resuscitation, 2.5 ± 0.4; extracorporeal cardiopulmonary resuscitation, 2.4 ± 0.2; CO-E-CPR, 1.4 ± 0.2; p < 0.05) expression were reduced after carbon monoxide exposure. Conclusions: Carbon monoxide application during extracorporeal resuscitation reduces injury patterns in neuromonitoring and decreases histopathologic cerebral damage by reducing apoptosis. This may lay the basis for further clinical translation of this highly salutary substance. Abstract : Supplemental Digital Content is available in the text.